Decentralised control of parallel inverters connected to microgrid using the derivative‐free non‐linear Kalman filter. Issue 7 (1st July 2015) - Rigatos, Gerasimos; Siano, Pierluigi; Zervos, Nikolaos; Cecati, Carlo
Abstract : Decentralised control for parallel inverters connected to the power grid is developed using differential flatness theory and the derivative‐free nonlinear Kalman filter. It is proven that the model of the inverters, is a differentially flat one. This means that all its state variables and the control inputs can be written as differential functions of a single algebraic variable which is the flat output. By exploiting differential flatness properties it is shown that the multiple inverters model can be transformed into a set of local inverter models which are decoupled and linearized. For each local inverter the design of a state feedback controller becomes possible. Such a controller processes measurements not only coming from the individual inverter but also coming from other inverters which are connected to the grid. Moreover, to estimate the non‐measurable state variables of each local inverter, the derivative‐free nonlinear Kalman filter is used. Furthermore, by redesigning the aforementioned filter as a disturbance observer it becomes also possible to estimate and compensate for disturbance terms that affect each local inverter.